A study on inventory control system practice in Kuantan food processing small medium enterprise (sme) - Nurul Ajilah, Mohamad Rosalan (2013)
New era and globalisation world that every challenge mind and our mind has made people rated medium rise by building medium small industry. Business that start on a small scale is a site to a company until market their products in world market. Medium Small Enterprise (SME) is very important in building national economy. Therefore, this thesis discuss research related system inventory management used by company under small medium Enterprise (SME). Objective this thesis is to identify problem which occurred in system inventory management used wear by bakery manually record and produce one management system inventory control use software Microsoft Excel. Decision found, this system successfully produced and can be recycled for inventory management that is more efficient and fast. Apart from that, this system can reduce rate additional cost for paper printing to record inventory and it can also save space. Furthermore, this system can reduce cost stock that is excess.